PENGUNAAN TEKNIK DISKUSI SECARA DARING UNTUK MENGEMBANGKAN KETERAMPILAN KOMUNIKASI INTERPERSONAL SISWA KELAS XI IPS 4 SMAN 1 BATUJAJAR - Nisya Amelia Sakti; Euis Eti Rohaeti; Riesa Rismawati Siddik (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2021)
Communication is not only about conveying the message content but can also determine the level of human interpersonal relationships. The Covid-19 pandemic that has occurred has made the government decide to study from home and students are asked to be able to adapt to new circumstances, which is one of the reasons for hampering interpersonal communication skills. The purpose of this study was to find out that group guidance services can be used to develop students' interpersonal communication skills. This study uses a qualitative approach with a descriptive method. Data collection techniques used are interviews and observations. The subjects of this study were 6 students of XI IPS 4 SMAN 1 Batujajar. Judging from the results with the provision of group guidance services agreed upon by the BK teacher and students for 3 meetings by formulating planning, implementation, evaluation and follow-up, the results obtained are that students are able to be open in telling stories, communicating with others, students becoming more responsive when communicating. and students can appreciate when communicating. The results showed that the provision of group guidance services can develop students' interpersonal communication skills.